Misunderstandings in Interpersonal and Inter-Professional Communication and their Impact On Health Outcomes and Patient Safety - Fatahi, Nabi (Archives of Clinical and Medical Case Reports, 2019)
Since clinical health communication is the basic stage in the process of diagnosis and treatment, adequate clinical interaction is essential between patients and healthcare providers, as well as between the clinicians involved. The healthcare communication modes that are the focus of this study are interpersonal and inter-professional encounters, which in both cases involve both oral and written communication. This paper will review the literature on factors influencing clinical encounters and their impact on health outcomes and patient safety. Inadequate oral and written communication leads to misunderstanding in clinical encounters, which causes patient insecurity. In addition to language and culture, as the main factors that influence communication outcome, professionalism, caring attitudes, time, respect and openness are additional factors that are frequently mentioned in this context. Oral communication between healthcare providers may be performed directly or through a third person (interpreter) who facilitates encounters in cases of a language barrier between patient and the caregiver. Mutual understanding in both interpersonal and inter-professional communication is very important for quality health care and patient satisfaction. Written misunderstandings are more visible in inter-professional encounters, whereas in interpersonal communication oral misunderstandings are more frequent. Cultural misunderstandings in clinical encounters may be rooted in individual, organizational or ethnic and cultural backgrounds. The last will be in focus in this study. Due to the importance of communication as the fundamental stage in diagnosis and treatment procedures, it is vital to prevent misunderstandings in communication between patients and caregivers during clinical encounters as well as between the clinicians involved.